2013
DOI: 10.1111/ppl.12052
|View full text |Cite
|
Sign up to set email alerts
|

Two cytosolic aldolases show different expression patterns during shoot elongation in Moso bamboo, Phyllostachys pubescens Mazel

Abstract: In fast-growing Moso bamboo (Phyllostachys pubescens Mazel), cytosolic fructose 1,6-bisphosphate aldolase (aldolase; EC 4.2.2.13) was more highly active in elongating tissues than in tissues that had already finished elongating. It is well known that the removal of the culm sheath prevents bamboo from elongating. When the sheath was removed from the culm, the aldolase activity was gradually reduced over time. Two isozyme genes for aldolase, PpAldC1 and PpAldC2, were cloned from the elongating tissues of Moso b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…However, there was also a high abundance of aldolase in the rhizosphere soils at 4-5 mm from the root surface where the soil is anaerobic. Lao et al (2013) reported that aldolase induced under these conditions, and its activity rapidly decreased following the transition of plants to aerobic conditions. The anaerobic biodegradation of PAHs is a slow process, and the biochemical mechanisms involved have not yet been fully elucidated (Haritash and Kaushik 2009).…”
Section: Changes Of Reconstructed Metagenomes In Rice Rhizosphere Durmentioning
confidence: 99%
“…However, there was also a high abundance of aldolase in the rhizosphere soils at 4-5 mm from the root surface where the soil is anaerobic. Lao et al (2013) reported that aldolase induced under these conditions, and its activity rapidly decreased following the transition of plants to aerobic conditions. The anaerobic biodegradation of PAHs is a slow process, and the biochemical mechanisms involved have not yet been fully elucidated (Haritash and Kaushik 2009).…”
Section: Changes Of Reconstructed Metagenomes In Rice Rhizosphere Durmentioning
confidence: 99%
“…Lao et al . () reported that aldolase induced under these conditions, and its activity rapidly decreased following the transition of plants to aerobic conditions. The anaerobic biodegradation of PAHs is a slow process, and the biochemical mechanisms involved have not yet been fully elucidated (Haritash and Kaushik ).…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, the expression levels of chloroplast development-related genes Cab1R and Cab2R, which encode two light-harvesting Chl a/b-binding proteins of PSII [27], and psaA and psbA, which separately encode two reaction center polypeptides of PSI and PSII, were also significantly down-regulated (Fig. 3A).…”
Section: Osald-y Affects the Photosynthetic Rate And Chl Biosynthesismentioning
confidence: 88%